POTENSI SUMBERDAYA KAMPUNG AIPIRI DISTRIK MANOKWARI TIMUR KABUPATEN MANOKWARI: Potential Resources of Aipiri Village District East Manokwari Manokwari Regency - Andoyo Supriyantono; Barahima Abbas; Rein M. R. Ruimassa; Yolanda Holle; Amestina Matualage; Nouke L. Mawikere; Alce I. Noya; Ishak Musaad; Febriza Dwiranti; Rina A. Mogea; Soetjipto Moeljono; Roni Bawole; Syafrudin Raharjo; Yuanike Kaber; Hendri Hendri; Martha Kayadoe; Paulus Boli; Gandi Y. S. Purba; Yafed Syufi (Fakultas Peternakan Universitas Papua, 2022)
ABSTRACT Community service activities have been carried out by a team of lecturers from the Postgraduate Program in Aipiri to identify regional potential and human resource potential. The activity was carried out at the village hall which was followed by field visits to both residents' houses and agricultural land, forestry and the sea. Sampling of respondents was carried out randomly by considering the ownership of the resources owned. The results show that there are two existing agricultural conditions, namely 1) Agricultural Conditions at an Altitude > 10 m with green bean plants dominant; 2). The altitude of the place is 6 m above sea level (residential settlement) with flower plants, vegetables and plant sources of carbohydrates, areca nut and betel. The forest area is included in the tropical forest, 75% is natural forest and 25% is artificial forest. Livestock developed by the community in Aipiri are pigs with more males than females. Fisheries activities in Aipiri are still in the form of traditional activities. The fishing grounds for fishermen only reach the waters in front of the village, using rowboats without motors. The people who inhabit Aipiri are grouped into heterogeneous communities because there has been an assimilation of various ethnicities, including the Biak, Serui, MPur, Javanese, Wandamen and Meyah ethnic groups. The social interaction that exists between community members is manifested through government, spiritual, economic, and educational activities. Aipiri is located on the northern coast of Bird's Head which is directly adjacent to the Pacific Ocean. Keywords: Aipiri; Human resources; Potential; Natural resources ABSTRAK Kegiatan pengabdian pada masyarakat telah dilakukan oleh tim dosen Program Pascasarjana di kampung Aipiri untuk mengidentifikasi potensi wilayah dan potensi sumberdaya manusia. Kegiatan dilaksanakan di balai Desa yang dilanjutkan dengan kunjungan lapang baik di rumah-rumah warga maupun lahan pertanian, Kehutanan maupun laut. Pengambilan sampel responden dilakukan secara acak dengan mempertimbangkan kepemilikan sumberdaya yang dimiliki. Hasil kegiatan menunjukkan bahwa terdapat dua kondisi existing pertanian yaitu 1) Kondisi Pertanian pada Ketinggian Tempat > 10 m dengan dominan tanaman kacang hijau; 2). Ketinggian tempat 6 m dpl (pemukiman penduduk) dengan tanaman bunga, sayuran dan tanaman sumber karbohidrat, pinang dan sirih. Kawasan hutan termasuk dalam hutan tropis yaitu 75 % merupakan hutan alam dan 25% merupakan hutan buatan. Ternak yang dikembangkan oleh masyarakat di Kampung Aipiri adalah ternak babi dengan jenis kelamin jantan lebih banyak dari pada betina. Kegiatan perikanan di Desa Aipiri masih berupa kegiatan tradisional. Daerah penangkapan nelayan hanya sampai di perairan depan desa, dengan menggunakan perahu dayung tanpa motor. Masyarakat yang mendiami Kampung Aipiri dikelompokan ke dalam masyarakat heterogen karena sudah terjadi pembauran berbagai etnis antara lain etnis Biak, serui, Mpur, Jawa, Wandamen dan Meyah. Interaksi sosial yang terjalin antar warga masyarakat diwujudkan melalui aktifitas pemerintahan, kerohaniaan, perekonomian, dan pendidikan. Kampung Aipiri berada di pinggiran pantai utara di Kepala Burung yang berbatasan langsung dengan Laut Pasifik. Bagian utara Kepala Burung Papua telah mengkondisikan wilayah pesisir dan perikanan menjadi rentan terhadap dampak ekor dari siklon tropis dan topan yang berasal dari Samudera Pasifik yang berkaitan erat dengan gelombang badai dan hujan deras. Kata kunci: Aipiri; Potensi; Sumberdaya alam; Sumberdaya manusia